Spontaneous regression of a systemic ALK (+) anaplastic large cell lymphoma carrying ALK gene rearrangement that developed after PPD tuberculin skin test - Beköz, Hüseyin Saffet; Kantarcıoğlu, Bülent; Tecimer, Tülay; Sargın, Deniz (Taylor & Francis, 2015)
Here we report an ALK ( ) ALCL carrying ALK gene rearrangement that developed after a PPD tuberculin skin test, which spontaneously regressed after an excisional lymph node biopsy and is still in complete remission more than 5 years later without treatment. Written informed consent was obtained from the patient for publication of this manuscript and accompanying images.
Keywords: Spontaneous; Rearrangement; Tuberculin